(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In the face of uncertainties in science policy, in recent years the European legislator has combined reflections coming from post-normal science and from the idea of co-production between science and policy to build more open and transparent public decisions. But the science for policy is still often fragmented between the European and national levels, where opaque policy choices are legitimized by presumed scientific objectivity and certainty. The Italian stories of a teratogenic drug, thalidomide, and a rare genetic disease with a very expensive therapy, XLH, reflect and exemplify such fragmentation and opacity.